Diagnostic Accuracy of Clinical Tests for Subscapularis Tears: A Systematic Review and Meta-analysis. Issue 9 (24th September 2021) - Lädermann, Alexandre; Collin, Philippe; Zbinden, Olivia; Meynard, Timon; Saffarini, Mo; Chiu, Joe Chih-Hao
Background: Previous systematic reviews and meta-analyses on the diagnostic accuracy of shoulder clinical tests do not reach conclusions regarding subscapularis tears. Purpose: To compare the diagnostic accuracy of commonly used clinical tests for subscapularis tears. Study Design: Systematic review; Level of evidence, 3. Methods: An electronic literature search was conducted using Medline, Embase, and the Cochrane Library/Central. Eligibility criteria were original clinical studies reporting the diagnostic accuracy of clinical tests to diagnose the presence of rotator cuff tears involving the subscapularis. Results: The electronic literature search returned 2212 records, of which 13 articles were eligible. Among 8 tests included in the systematic review, the lift-off test was most frequently reported (12 studies). Four tests were eligible for meta-analysis: bear-hug test, belly-press test, internal rotation lag sign (IRLS), and lift-off test. The highest pooled sensitivity was 0.55 (95% CI, 0.28-0.79) for the bear-hug test, while the lowest pooled sensitivity was 0.32 (95% CI, 0.13-0.61), for the IRLS. In all tests, pooled specificity was >0.90. Conclusion: Among the 4 clinical tests eligible for meta-analysis (bear-hug test, belly-press test, IRLS, and lift-off test), all had pooled specificity >0.90 but pooled sensitivity <0.60. No single clinical test is sufficiently reliable to diagnose subscapularis tears. Registration: PROSPERO (CRD42019137019).